Central airway obstruction caused by adenoid cystic carcinoma in pregnancy: a case report and review of the literature. Issue 5 (20th April 2018) - Shafiee, Samaneh; Adno, Alan; French, Bruce; Johansson, Cherynne; Frankel, Anthony; Williamson, Jonathan P.
Abstract : We present a case of tracheal adenoid cystic carcinoma (ACC), a rare type of primary airway tumour, diagnosed in a pregnant lady. We also discuss the characteristics and treatment of 13 other cases of primary tracheal tumours reported during pregnancy, 2 cases of which were ACC. Abstract : Malignancy complicates one in a thousand pregnancies. The most frequently diagnosed of these are breast, cervical, melanoma, ovarian, and haematological neoplasms. Tumours of respiratory origin are very uncommon during pregnancy. We present a case of tracheal adenoid cystic carcinoma (ACC), a rare type of primary airway tumour, diagnosed in a pregnant woman. To our knowledge, this is the third reported case of tracheal ACC complicating pregnancy. We discuss potential barriers to timely diagnosis of malignancies during pregnancy and consider optimal management strategies, taking into account the potential harm to the mother and foetus in a field with a limited evidence base.